2011
DOI: 10.1590/s0100-29452011000400006
|View full text |Cite
|
Sign up to set email alerts
|

Effects of modified atmosphere packaging on ripening of 'Douradão' peach related to pectolytic enzymes activities and chilling injury symptoms

Abstract: The present study evaluated the effects of modified atmosphere packaging on inhibition of the development of chilling injury symptoms in 'Douradão' peach after cold storage and the possible involvement of cell wall enzymes. Fruits were harvested at the middle stadium of ripening, packed in polypropylene trays and placed inside low density polyethylene (LDPE) bags (30, 50, 60 and 75 µm of thickness) with active modified atmosphere (10 kPa CO2 + 1.5 kPa O2, balance N2). The following treatments were tested: Cont… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
7
0
1

Year Published

2012
2012
2021
2021

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 11 publications
(9 citation statements)
references
References 24 publications
1
7
0
1
Order By: Relevance
“…This principle is a critical component for successful application of individual wrapping as observed in the present study also (De Santana et al 2011). However ethylene measurement was not included in experiment which may further elaborate respirational activities associated with low temperature storage.…”
Section: Discussionmentioning
confidence: 82%
“…This principle is a critical component for successful application of individual wrapping as observed in the present study also (De Santana et al 2011). However ethylene measurement was not included in experiment which may further elaborate respirational activities associated with low temperature storage.…”
Section: Discussionmentioning
confidence: 82%
“…studies have reported the inhibiting effect of MAP on activities of cell wall degradation related enzymes. 31,32 Thus, the delay of the fruit firmness decline under MAP treatments may be a result of the slower degradation of the cell walls compared to the control fruit. SSC of the green hull showed a two-peak trend (Fig.…”
Section: Firmness and Ssc Of The Green Hull Decay Incidence Of Freshmentioning
confidence: 99%
“…Este aumento representativo de la tasa respiratoria durante la maduración genera cambios en la concentración de almidón y ácidos orgánicos, los cuales pueden ser utilizados como sustratos respiratorios (Akbudak y Eris 2004). De acuerdo con Brovelli et al (1999), durante la maduración el durazno presenta una tasa respiratoria moderada con valores entre 59 a 102 mg CO 2 kg -1 h -1 ; según Santana et al (2011) para durazno 'Douradão' la tasa de respiración fue de 95 mg CO 2 kg -1 h -1 al inicio de la maduración, y alcanzó valores entre 120-130 mg CO 2 kg -1 h -1 a medida que avanzó el proceso.…”
Section: Patrón De Respiración Y Producción De Etilenounclassified